Brain atrophy can introduce age‐related differences in BOLD response. Issue 7 (11th April 2017) - Liu, Xueqing; Gerraty, Raphael T.; Grinband, Jack; Parker, David; Razlighi, Qolamreza R.
Abstract: Use of functional magnetic resonance imaging (fMRI) in studies of aging is often hampered by uncertainty about age‐related differences in the amplitude and timing of the blood oxygenation level dependent (BOLD) response (i.e., hemodynamic impulse response function (HRF)). Such uncertainty introduces a significant challenge in the interpretation of the fMRI results. Even though this issue has been extensively investigated in the field of neuroimaging, there is currently no consensus about the existence and potential sources of age‐related hemodynamic alterations. Using an event‐related fMRI experiment with two robust and well‐studied stimuli (visual and auditory), we detected a significant age‐related difference in the amplitude of response to auditory stimulus. Accounting for brain atrophy by circumventing spatial normalization and processing the data in subjects' native space eliminated these observed differences. In addition, we simulated fMRI data using age differences in brain morphology while controlling HRF shape. Analyzing these simulated fMRI data using standard image processing resulted in differences in HRF amplitude, which were eliminated when the data were analyzed in subjects' native space. Our results indicate that age‐related atrophy introduces inaccuracy in co‐registration to standard space, which subsequently appears as attenuation in BOLD response amplitude. Our finding could explain some of the existing contradictory reports regarding age‐related differences in the fMRI BOLD responses. Hum Brain Mapp 38:3402–3414, 2017 . ©2017 Wiley Periodicals, Inc.